EVALUATION OF DEGRADATION BY-PRODUCTS OF HERBICIDE AMETRIN OBTAINED BY ADVANCED OXIDATIVE PROCESSES - Rocha, R.S.; Beati, A.A.G.F.; Valim, R.B.; Steter, J.R.; Bertazzoli, R.; Lanza, M.R. V. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Alternative technologies, such as advanced oxidative processes (AOP), contribute to the control of environmental pollution and in this context one of the most important information is the determination of degradation by-products formed in each study condition. In this work, different H2O2concentrations, pH and temperature were evaluated, with the objective of promoting the breakdown of the molecule of the triazine herbicide ametryn and to evaluate the main by-products formed in the degradation process. Thelargest number of by-products was identified using direct insertion mass spectrometry under conditions with 20% and 25% H2O2at 65 °C. Five possible compounds were detected from the fragmentation of the original ametryne molecule.